Symbolic meanings of Jako Se Ruko ritual equipment in Tidore marriage tradition - Suddin M. Saleh Djumadil (Universitas Dian Nuswantoro, 2025)
This study identifies and analyses the symbolic meanings of the ritual paraphernalia used in Jako Se Ruko, a marriage tradition of the Tidore community. Drawing on Ogden and Richards’ semiotic triangle framework of the nature of meaning, this study employs a descriptive, qualitative method with a semantic approach. Data collection was conducted through field observations, utilising semi-structured interviews, audio-visual recordings, and comprehensive documentation. The research was carried out across four sub-districts in the Tidore Islands: South Tidore (specifically in Tongowai and Gurabati villages), North Tidore (Mareku village), Central Tidore (Seli and Soa Sio villages), and East Tidore (Dowora village). The findings reveal that the Jako Se Ruko ritual in Tidore wedding traditions serves as a ceremonial warding-off-evil bath (mandi tolak bala), aimed at purifying both the bride and groom prior to the Islamic marriage solemnization (akad nikah). Furthermore, the interpretations of the ritual paraphernalia predominantly lean toward associative meanings, wherein each object symbolises or is associated with distinct cultural values. In this context, these associative meanings primarily correlate with spiritual endeavours, signifying the prospective couple's physical purification and inner tranquillity. Ultimately, while all linguistic symbols within the ritual possess a referent, they lack a direct referential meaning.